Pengaruh Literasi Keuangan, Digital Payment, Media Sosial Terhadap Perilaku Konsumtif Mahasiswa Universitas Palangka Raya - Oktami Nabella Tanjung; Solikah Nurwati; Katarina Rani Rajagukguk; Nia Adelina Br Bangun (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
The increasing trend of consumptive behavior among university students in the digital era has become a critical concern requiring comprehensive analysis. The core issue of this study lies in the high level of student consumption behavior that is disproportionate to their financial literacy, further intensified by the ease of digital payments and the influence of social media. This research aims to analyze the effects of financial literacy, digital payment, and social media on the consumptive behavior of students at Universitas Palangka Raya. A quantitative research approach was employed, involving the distribution of Likert-scale questionnaires to 202 students selected through non-probability sampling. The data were processed using multiple linear regression with SPSS version 25, including validity and reliability testing, classical assumption testing (normality, linearity, multicollinearity, heteroscedasticity, and autocorrelation), as well as t-tests and F-tests. The findings reveal that digital payment and social media have a positive and significant impact on consumptive behavior, with social media emerging as the most influential factor. Conversely, financial literacy has a negative but statistically insignificant effect. The regression model explains 37.6% of the variation in students’ consumptive behavior, with the remaining 62.4% influenced by external factors not included in the model. These results underscore the importance of practical financial education, increased awareness of digital financial tools, and critical engagement with social media to mitigate excessive consumption tendencies among students in today’s digital consumption culture.